RETRACTED: Penanaman Karakter Anak Usia 5-6 Tahun di TK Pertiwi Pakualaman (Studi Kasus pada Taman Kanak-Kanak Pertiwi Pakualaman Yogyakarta, tahun 2018) - Novianti Retno Utami; Windi Wulandari Iman Utama (SALIHA: Jurnal Pendidikan & Agama Islam, 2019)
RETRACTED Following a rigorous, carefully concerns and considered review of the article published in Saliha : Jurnal Pendidikan dan Agama Islam  entitled "Penanaman Karakter Anak Usia 5-6 Tahun di TK Pertiwi Pakualaman (Studi Kasus pada Taman Kanak-Kanak Pertiwi Pakualaman Yogyakarta, tahun 2018),” Vol. 2 No. 1 (2019), Pp. 69-100, http://staitbiasjogja.ac.id/jurnal/index.php/saliha/article/view/21. This paper has been found to violate the principles of publication in Saliha : Jurnal Pendidikan dan Agama Islam and has been retracted.  Editors find double publications due to the similarity of the content of articles published in the Journal Obsesi: Jurnal Pendidikan Anak Usia Dini, entitled “Nilai Filosofis Sestradi Puro Pakualaman Yogyakarta Sebagai Dasar Pendidikan Karakter Anak Usia Dini”, Vol. 6, No. 5 (2022), Pp. 4820-4830, https://obsesi.or.id/index.php/obsesi/article/view/2641. Thus this article contains elements of scientific violations.  The editor apologized to the journal readers  for negligence during the submission process.